Analisis Kinerja Petugas Aviobridge Saat Peak Season di Bandar Udara Internasional I Gusti Ngurah Rai - Ni Kadek Dwi Yunita Sari; You She Melly Anne Dharasta (Ebisnis Manajemen, 2025)
This study is entitled Analysis of Aviobridge Officer Performance During the Peak Season of Lebaran at I Gusti Ngurah Rai International Airport, Bali. The purpose of this study is to determine the performance of aviobridge officers and what obstacles they face during the peak season of Lebaran. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the performance of aviobridge officers is included in the good category based on five indicators, namely quality, quantity, punctuality, effectiveness, and independence. Obstacles faced during the peak season include increased flight volume, technical problems with the aviobridge system, weak communication signals, limited operational vehicles, and bad weather. However, officers can still carry out their duties professionally and in accordance with standard operating procedures (SOP). This study is expected to be an input for related parties in improving service and operational efficiency, especially during busy periods.